Living Alone and Discharge to Skilled Nursing Facility Care after Hospitalization in Older Adults. Issue 1 (26th October 2017) - Lage, Daniel E.; Jernigan, Michael C.; Chang, Yuchiao; Grabowski, David C.; Hsu, John; Metlay, Joshua P.; Shah, Sachin J.
Abstract : Background/Objectives: Community‐based older adults are increasingly living alone. When they become ill, they might need greater support from the healthcare system than would those who live with others. There also has been a growing concern about the high use of postacute care such as skilled nursing facility (SNF) care and the level of variation in this use between hospitals and regions. Our objective was to examine whether living alone contributed to the risk of being discharged to a SNF. Design: Retrospective cohort study. Setting: Massachusetts General Hospital. Participants: Community‐dwelling individuals aged 50 and older admitted to the medical service and discharged alive between July 2014 and August 2015 (N = 7, 029). Measurements: We extracted demographic, clinical, and functional data from the electronic medical record and used multivariable logistic regression to determine whether living alone at the time of hospitalization was associated with subsequent discharge to a SNF. Results: Of eligible individuals, 24.8% reported living alone before admission. Those living alone were more likely to be female, older, and more independent before admission than those living with others. Of all participants, 10.9% were discharged to a SNF. After adjustment, participants living alone had more than twice the odds of being discharged to a SNF (odds ratio = 2.23, 95% confidence interval = 1.85–2.69, P < .001). Discussion: People living alone are more likely to be discharged to SNFs, even when compared to other individuals with similar levels of clinical complexity and functional status. To the extent that this variation is due to a lack of home support, it could be possible to reduce SNF use through additional home services after hospital discharge.